HUBUNGAN PENERAPAN ISO 9001:2000 DAN ORGANISASI BELAJAR TERHADAP KINERJA STAF - Elais Retnowati; Sutaryat Trisnamansyah (Jurnal Ilmiah Visi, 2010)
The objective of this research is to analyze the relationship of ISO 9001:2000 implementation with the learning organization and the staff performance in an institution. This study is conducted in P2PNFI Region I Jayagiri and P2PNFI Region II Semarang. The design of development strategies on this research are: (1) conducting the beginning study; (2) creating research instruments; (3) testing instruments; (4) analyzing the validity and reliability instruments; (5) distributing questioners to 94 respondents at P2PNFI Regional I Jayagiri and 84 respondents at P2PNFI Regional II Semarang; (6) collecting questioners; (7) data input and processing; (8) conducting data analyzing and (9) wrapping up the conclusion. The research reveals that (1) there is an increase of the staff performance; (2) a positive correlation between the implementation of ISO 9001:2000 with the staff performance; (3) a positive relationship between the learning organization with the staff performance and (4) a correlation between the implementation of ISO9001:2000 with the performance of staff at two institutions.